Paluparan han Borongan redeveloping Borongan Airport into a tourism-generative Hybrid Estate as a Gateway to Eastern SamarPaluparan han Borongan: Redeveloping Borongan Airport into a Tourism-generative hybrid estate as a gateway to Eastern Samar - Abing, Jean Kelly; Lacson, David Xander T. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
The Paluparan han Borongan (Airport of Borongan) serves as the sole commercial
airport in the province of Eastern Samar after recently resuming biweekly operations
succeeding years of hiatus. Accessibility is vital in the success of the tourism
campaigns of a locality, especially for Eastern Samar, which belongs to a primarily
agricultural region currently ranked as the third lowest in terms of GDP per capita in
the Philippines in 2023. While the agriculture, forestry, and fishing industries trail
last in GDP growth rates at 0.5%, the accommodation and food service industries
lead at 32.1%, presenting an opportunity for the province to further bolster their
economic profile by incorporating these industries into the development plan through
tourism. Borongan Airport in Punta Maria poses development potential due to its
central location in the province capital and its proximity to the top tourist attraction
of the city. At its current capacity, the airport’s facilities may not be able to
accommodate the impending influx of passengers once the province’s tourism
campaign is underway, as it is envisioned to facilitate the majority of domestic flights
for tourist and local passengers inbound for Eastern Samar. The airport is to be
developed into a hybrid tourism estate with transportation infrastructure adjoined by
harmonious commercial, cultural, and recreational facilities. The estate is to address
the inherent climatic vulnerabilities through adaptive spatial configurations,
renewable energy, and vernacular materials, while also embodying the local essence
of Borongan through cultural imagery and materials.
Include appendices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Airports -- Borongan (Eastern Samar); Airport facilities -- Borongan (Eastern Samar); Airport terminals -- Borongan (Eastern Samar)